Effects of dietary L-Citrulline supplementation on growth performance, meat quality, and fecal microbial composition in finishing pigs - Du, Junhua; Gan, Mailin; Xie, Zhongwei; Zhou, Chengpeng; Jing, Yunhong; Li, Menglin; Liu, Chengming; Wang, Meng; Dai, Haodong; Huang, Zhiyang; Chen, Lei; Zhao, Ye; et al. (Frontiers in Microbiology, 2023)
Gut microbiota plays important roles in gut ecology and development of pigs, and which is always regulated by nutrients. Here we investigated the effect of L-Citrulline on growth performance, carcass characterizes as well as its potential regulatory mechanism. The results showed that 1% dietary L-Citrulline supplementation for 52 days significantly increased final weight, liveweight gain, carcass weight and average backfat and markedly decreased drip loss (P<0.05) of finishing pigs compared with the control group. Microbial analysis of fecal samples revealed a marked increase in α-diversity and significantly altered composition of gut microbiota in finishing pigs in response to L-Citrulline. In particular, these altered gut microbiota at the phylum and genus level may be mainly involved in metabolic process of carbohydrate, energy and amino acid, and exhibited a significant association with final weight, carcass weight and backfat thickness. Taken together, our data revealed a potential role of L-Citrulline in modulation of growth performance, carcass characterizes and meat quality of finishing pigs, which is most likely associated with gut microbiota.